EFFECT OF ENTREPRENEURIAL CULTURE ON EMPLOYEE PERFORMANCE IN WORLD VISION - WYNNE, WANJIKU NJUGI-; AGUSIOMA, NICKSON LUMWAGI (IJRDO - Journal of Business Management, 2017)
The concept of “entrepreneurial culture” has existed for decades, described as an organizational culture embodying and championing entrepreneurial characteristics and attributes. These characteristics have included risk taking, innovation and creativity, the elements one would expect to see among entrepreneurs as individuals. (Wong, 2014). This study examined the characteristics of entrepreneurial culture and their effect on employee performance in World Vision Kenya (WVK). The study sought to test the null hypothesis: Entrepreneurial culture has no significant effect on employee performance in the world vision and adopted a descriptive research design using questionnaires administered to the employees of WVK to collect data. A total of 484 employees were sampled from a target population of 960. The data was subjected to descriptive and inferential analysis using SPSS (ver.20). The Analysis of variance (ANOVA) was used to calculate the regression model significance which indicated there was a significant relationship between entrepreneurial culture and employee performance. Findings revealed that entrepreneurial culture within the organization impacts positively on employee performance and therefore, the study recommends that Management at WVK continue to encourage and improve on their entrepreneurial culture because it has been found to improve on employee performance in the organization